Effect of freezing rate and storage time on quality parameters of strawberry frozen in modified and home type freezer - Yanat, Murat; Baysal, Taner (2019)
Freezing rate and storage time are the most important parameters in the losses of bioactive compounds of food during the freezing process. For this reason, the quality of strawberries which were frozen at different freezing mediums and the effect of storage time on samples were investigated in this research. The freezer section of the domestic refrigerator was used for slow freezing. Besides that, a modified freezer cabinet which capable of blowing air at a speed of 1.2 m/s at -30°C designed and produced by Bosch und Siemens Hausgerate GmbH (Çerkezköy,Turkey) was used for quick freezing. In the quick freezing chamber inside the refrigerator, the samples were provided to be frozen with a higher freezing speed than the static freezing unit of the refrigerator. Freezing time and freezing rates were determined from the cooling curves obtained experimentally. Slow and quick frozen samples were stored at −25°C for 4 months. Drip loss, total phenolic content, ascorbic acid content and total monomeric anthocyanin content of samples were significantly different after freezing and during storage time. It has been determined that higher freezing rate is essential for the better preservation of bioactive compounds of the strawberries. Freezing should be done at an appropriate freezing rate to preserve the cell structure and the nutritional content of strawberries.
Bibliografija: str. 157-158.
Abstract.
Keywords: Jagoda -- Zamrzavanje -- Stopa zamrzavanja -- Skladištenje -- Kvaliteta jagoda -- Fenoli